HUKUM MENGULANG SHALAT DENGAN BERJAMA’AH (STUDI PEMAHAMAN HADIS MUKHTALIF) - Febriyeni Febriyeni; Beni Firdaus (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
I’adah (repeating prayer) is to repeat the implementation of an obligation in time according to the provisions of the sharak for the second time due to the occurrence of shortages or aging in the implementation of the first obligation. In the matter of repeating this prayer, the existence of the traditions of the Prophet Muhammad explained about the ability to repeat prayers in congregation, meaning someone who had prayed at his house, then he went to the mosque and found a congregation who would pray, he was allowed to repeat pray by joining the congregation. However, in other traditions, indications of prohibition were found to repeat the same prayer on one day even with congregations. The two versions of the hadith appear to be textually contradictory, but as Imam Shafi'i's statement states that the traditions of the Prophet Muhammad will not be contradictory, a solution can be found so that a proper understanding of the traditions that appear to be contradictory can be found. Therefore, it is necessary to analyze a complete understanding of the traditions of repeating prayers in congregation so that the law can be repeated in congregation.